Trampas de la pobreza municipales en México: ¿economía o política? - Millán Valenzuela, Henio Gonzalo (Intersticios Sociales, 2018)
Las trampas de la pobreza suelen ser frecuentes en los municipios mexicanos, pero no en todos. Su presencia depende de variables económicas y políticas. Entre las primeras sobresalen la productividad laboral; entre las segundas, el grado de democratización y la eficacia y eficiencia de los gobiernos estatales. El artículo trata de clarificar cuál de todas ellas es la más relevante. Concluye que es el bajo grado centralización democrática de los estados lo que explica la existencia de la trampas de la pobreza. Poverty traps at the municipal level in Mexico: economy or politics? Poverty traps are frequent in Mexican municipalities, though not in all of them. Their presence depends on variables both economic and political in nature. Among the first, labor productivity stands out; while in the second, the degree of democratization and the efficiency of state governments play important roles. This article seeks to clarify which of these factors are most important. It concludes that the low degree of democratic centralization in individual states is what best explains the existence of poverty traps. Keywords: traps, poverty, institutions democracy, municipalities.